FLUID REGULATION AND ADH IN RAT OESTROUS: THE EFFECTS OF OESTRADIOL - Khan, Muhammad Azhar; Aslam, Muhammad (Journal of Ayub Medical College Abbottabad, 1996)
To determine how fluctuations in vasopressin are related to fluid ha la nee, studies were carried out in ovariectomized Sprague-Dawley rats injected daily with either vehicle or oestradiol benzoate (50, µg/rat) for 14 days. The animals were housed individually under 12 h light/12 h dark regimen with free access to food and water. Inputs & outputs were recorded and urine samples obtained to determine volume and osmolality. Plasma vasopressin levels were determined by radioimmunoassay. In the oestradiol benzoatetreated rats, food and water intakes were reduced during both dark and light periods compared with vehicletreated rats. Urine output showed a similar pattern of changes and appeared to be related to the vasopressin concentrations. Urine osmolality also correlated with the plasma vasopressin levels. These results indicate water retention in oestradiol benzoate-treated rats, and that oestradiol-induced increase in vasopressin may play a role in this fluid retention.